ANALISIS PENGUNGKAPAN PELAPORAN SEGMEN SESUAI PSAK 108 - Yovita Ariani; Debora Magdalena Sundayana; Aurellia Regina Rhadif; Natanael Tresno Leonardo (JURNAL LENTERA AKUNTANSI, 2024)
Financial statements are complex as they contain essential information about a company, presented accurately and accountably. Financial statements are used to provide relevant financial information to stakeholders. One critical aspect of financial statements is the disclosure of operating segments, which includes information about business performance based on specific activities or geographic areas. Accounting standards, such as PSAK 5, which was renumbered to PSAK 108, require companies to disclose their operating segments if those segments are deemed material and relevant. The population used in this study comprises all companies operating in the transportation infrastructure sub-sector with financial statements available for the year 2023. Data collection was conducted using secondary data with a purposive sampling technique. The sample size for this study is 8 companies. This study applies three tests to determine reportable segments: the ten percent revenue test, the ten percent profit or loss test, and the ten percent total assets test. Based on the research on segment reporting disclosure in the transportation infrastructure sub-sector, it was found that most companies in this sector have started disclosing segment information in accordance with applicable regulations. However, there are still some challenges in implementing comprehensive and detailed disclosure. The disclosures generally include data on revenues, profit/loss, as well as assets and liabilities for each relevant segment.